HSP20 Exerts a Protective Effect on Preeclampsia by Regulating Function of Trophoblast Cells Via Akt Pathways. (July 2019) - Li, Fanfan; Xie, Yin; Wu, Yuanyuan; He, Mengzhou; Yang, Meitao; Fan, Yao; Li, Xuanxuan; Qiao, Fuyuan; Deng, Dongrui
Preeclampsia (PE) remains the leading cause of maternal and fetal morbidity and mortality. Excessive apoptosis of the placenta and poor remodeling of spiral arteries caused by insufficient invasion of trophoblast cells into uterus have been implicated in the pathogenesis of PE. Accumulating evidence showed that heat shock protein 20 (HSP20) is closely associated with the proliferation, apoptosis, and metastasis of tumor cells. However, little is known about whether HSP20 plays a role in the development of PE. In this study, we detected the apoptosis index and the expressions of HSP20 and apoptosis-associated proteins in the placentas from PE and normal pregnancies. We found that HSP20 was reversely related to the apoptosis rate and the levels of proapoptotic proteins. Moreover, we identified that HSP20 could suppress the proliferation and apoptosis of trophoblast cells, turning them into a more invasive phenotype. Additionally, H2 O2 -induced oxidative stress was significantly alleviated, and several key proteins on the Akt signaling pathway were upregulated in HSP20-overexpressing trophoblast cells. These findings strongly suggested that HSP20 might play a role in the remodeling of spiral arteries through affecting the invasiveness of extravillous trophoblast cells via Akt signaling pathway, and the dysregulation of it might contribute to the pathophysiology of PE.